Reflectance Confocal Microscopy Combined with Dermoscopy and Histology in the Diagnostic Setting of Pigmented Eccrine Poroma: a Retrospective Study - Federico Venturi; Stephano Cedirian; Martina Mussi; Aurora Alessandrini; Emi Dika (Mattioli1885, 2024)
Introduction: Pigmented eccrine poroma (PEP) is a unique variant of a benign adnexal tumor known as eccrine poroma. Distinguishing PEPs from other pigmented lesions can be challenging due to overlapping clinical and dermoscopic features. Objectives: To provide a comprehensive analysis of the dermoscopic, confocal (RCM), and histological features of PEPs. Methods: We undertook a retrospective study of the clinical, dermoscopic, RCM and histopathological features of PEPs that were surgically excised and histopathologically recognized. Data on epidemiological, clinical, dermoscopic, RCM and histopathological features were collected from the databases of the Skin Cancer Unit, IRCCS Policlinico di Sant'Orsola, between January 2021 and May 2023. Results: The study population consisted of 61 patients, including 34 females (55.7%) and 27 males (44.3%). Dermoscopic examination of 61 PEPs revealed the presence of irregular borders (55.7%), milia-like cysts (50.8%), brown pseudo-network (41%), cerebriform pattern (34.4%), comedo-like openings (29.5%), atypical vessels (26.2%), glomerular vessels (18%), fingerprint-like perifollicular structures (8.2%), dots (4.9%) and dotted vessels (4.9%). RCM imaging was collected from 11 cases and showed mostly well-defined tumor nests with small cells in 100% of cases, bright structures in the upper dermis representing melanocytes and melanophages (63.6%), dark round spaces within the tumor nests (54.5%), well-demarcated borders of the nest (45.5%) and dilated and prominent vessels in upper dermis (27.3%). Histopathological pattern analysis revealed PEP sensu stricto (PEPss) as the most frequent (54.1%). Conclusions: The distinctive dermoscopic patterns, along with the confocal features aid in the differentiation from other pigmented lesions.